Determinants Allied To Information Channel Selection: A Review - Mehak Kapoor, Dr. Harpreet Singh (International Journal of Advanced Science and Technology, 2020)
Information is very crucial for the appropriate planning of the business activities and its proper implementation is equally important. In each area, information needs are recognized which is followed by the choice of the source/channel for searching the required information and after that the information is utilized to obtain the desired results. Information and communication technology (ICT) sources deliver customized as well as the latest information to the users to help them in making efficient and quick decisions. These sources help the users in getting information as per their convenience and have removed the impediments which come across in using Non-ICT sources. Instead of the availability of such types of sources, users prefer to avail of information from interpersonal sources such as Family, Friends, Fellow employees etc., Proper selection of information source is indispensable to acquire the information according to the necessity of the users. Information can be exchanged to the end-users through various means/channels and its selection depends upon various factors. Very few studies have clarified the factors associated with the selection of both types of sources i.e. ICT as well as Non-ICT sources. Therefore, channel focus and its scope are very narrow. No systematic review exists in the literature of information source selection for knowledge/information sharing. So, to fulfill this purpose, this study presented the review of empirical as well as review studies on information sources/channel selection in different contexts which identified authors, year of publication, countries, concepts, and methods. Various factors have been identified based on different theories and models such as Media Richness Theory, Marketing theory, Theory of Planned Behaviour, Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology (UTAUT), Cost/Benefit model, Least-Effort Model, etc. and also based on different papers reviewed. The study also offered some suggestions for future studies.